CODE SWITCHING AND READERS' PERCEPTIONS ON INTERNET ARTICLES OF KNOW-HOW RUBRIC IN PC MEDIA MAGAZINES - Wiranti Suryahutami, - (2011)
The present study is entitled Code Switching and Readers' Perceptions on 'Internet' Articles of 'Know-How' Rubric in 'PC Media' Magazine which investigates the code switching types and functions as well as the readers' perceptions on it. The data were collected from seven articles of Internet articles of Know-How rubric in PC Media magazines on January, March and April 2011. This study involved 30 students as respondents who were chosen randomly. Those respondents were presumably as readers of PC Media magazine and the users of computers and the Internet. The obtained data were classified based on Poplack's (1980, in Bullock and Toribio, 2009) and Myers-Scotton's (1989) code switching types and Koziol's (2000) code switching functions. Meanwhile, the questionnaire used in the articles was set based on Harnad's (1987) aspects of perception and Sobur's (2003) factors influencing perception. The study reveals that the code switching types found in the Internet articles are similar to the typology proposed by Poplack's (1980, in Bullock and Toribio, 2009) code switching types, i.e. tag switching, intra-sentential, and inter-sentential switching, and Myers-Scotton's (1987) code switching type, i.e. intra-word switching, with the intra-sentential as the most frequently occurring type. In addition, the code switching functions were found in a number of Koziol's (2000) i.e. interjection, personalization, quotation, reiteration, substitution, and untranslatability, with personalization function as the most frequently occurs. Based on the result of the gathered questionnaire, the data shows that the readers generally perceive the use of code switching in the Internet articles positively.